Audiens Framing : Peluang Baru dalam Penelitian Audiens - Twediana Budi Hapsari (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2013)
The study of the audience is one of the key studies in communication science. Audience studies are growing along with the development of communication technology itself, from face to face communication to the use of digital technologies in communications. The audience can not be separated from its context as a member of society and social environment. Therefore it can be understood that many factors influence the process of framing the audience (frames) an issue of the media, not only from personal knowledge and experience possessed by individual audience itself, but also other factors of the environment such as the opinion of a reference group in which the individual also be part of technology use in accessing the media. The process of forming a frame issue in the minds of the audience referred to as the process of framing by the audience (audience framing).